Answer:
This problem follow the associative property.
Explanation:
Let's recall that subtraction and division does not follow any property. However in this problem, there is also an addition. And that's the reason why we can prove and demonstrate the associative property of the addition and subtraction mixed in this problem, this way:
Let's prove for a = 1, b = 2, c = 3
3 * 1 + (2 * 2 - 3) = (3 * 1 + 2 * 2 ) - 3
3 + (4 - 3) = (3 + 4) - 3
3 + 1 = 7 - 3
4 = 4
Let's prove for a = 3, b = 4, c = 20
3 * 3 + (2 * 4 - 20) = (3 * 3 + 2 * 4 ) - 20
9 + (8 - 20) = (9 + 8) - 20
9 - 12 = 17 - 20
- 3 = - 3
Let's prove for a = 0, b = -5, c = 1
3 * 0 + (2 *-5 - 1) = (3 * 0 + 2 * -5 ) - 1
0 + (-10 - 1) = (0 + - 10) - 1
0 - 11 = -10 -1
-11 = - 11